ANALISIS PENGARUH SUHU TERHADAP WARNA, DENSITAS, DAN VISKOSITAS MADU HUTAN LEBAH Apis dorsata DARI KECAMATAN LUNYUK-SUMBAWA - Saputri, Nila Adelina; Pathiassana, Mega Trishuta; Gaibi, Nurul; Lestian; Nuriman; Septiani, Ayu Desi; Pathiussina, Rimba Trishuta (Jurnal Pengolahan Pangan, 2023)
Sumbawa is one of the regions in Indonesia which is famous as a producer of forest honey produced by Apis dorsata bees. The purpose of this study was to analyze the effect of temperature on the color, density, and viscosity of Apis dorsata bee forest honey originating from Lunyuk District, Sumbawa. This study used a completely randomized design (CRD) with temperature as a treatment factor. The results of the research show that temperature has a significant effect on the color, density, and viscosity of forest honey harvested around September 2021 at the beginning of the rainy season in the harvest area and its surroundings. Color testing using a calorimeter that produces a value of L*> 50 or light colored in various temperature treatments, namely 5oC, 26oC, and 35oC. Meanwhile, the density test showed the highest value, namely 1.48 g/m3 when the honey was at 5oC. Then, the highest viscosity value is 1.38 poise which also occurs when honey is at a temperature of 5oC. This shows that the best temperature for honey storage is 5oC compared to other temperature treatments.